Pemberdayaan Umat untuk Membangun Paroki Masa Depan - Pratama, Alvarado Putra Adi (Lux et Sal, 2023)
The complexity of the community structure in the context of the parish Church impacts the parish life and poses a challenge for every component of the Church. In light on this, the researcher intends to find a strategy to empower parishes in order to build the future parish. In the pursuit of empowerment, leaders play a vital role. In a parish, the role of a leader is typically assumed by the parish priests. An expected leader is one who practices servant leadership. Servant leadership can influence extra-role behavior so that it can encourage people to be actively involved in building Church services. Following the establishment of a leader with servant leadership, the question that arises now is how to empower the community. First, it is essential to develop a clear vision and mission for the parish which will provide it with a sense of direction and purpose. Next, the key elements of a parish that is poised to progress and develop are the empowerment of its human resources through the cultivation of friendship, care, trustworthiness, and openness to diversity. Some of these elements are essential for empowering the people in the light of the complexity of the times that need to be addressed through people empowerment. This empowerment is a long-term strategic program to strengthen parishes.